2007
DOI: 10.1038/sj.jp.7211876
|View full text |Cite
|
Sign up to set email alerts
|

Amnioinfusion in preterm PROM: effects on amnion and cord histology

Abstract: Objective: To investigate the effects of transabdominal amnioinfusion (TA) on the histology of amnion (A) and umbilical cord (UC).Study Design: From a cohort of 56 singleton pregnancies with premature rupture of membranes (PROM) at p24.6 weeks, we excluded those who did not develop severe oligohydramnios (n ¼ 12). Of the 44 patients, 29 consented to TA and 15 declined the procedure. TA was performed with normal saline solution.Result: Women who consented to TA underwent a median of three procedures had a gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The amniotic fluid is often replaced with warmed Ringer's lactate either during fetoscopy or following amniotic insufflation [27,78]. As Ringer's lactate has lower osmolarity than normal amniotic fluid, surgeons rely on fetal secretions (urine, lung, nasal, and salivary) and intramembranous reabsorption to normalize the amniotic fluid osmolarity after surgery [38,78,79,86,87]. The complete replacement of the amniotic fluid, after fetoscopy, is expected to take up to 48 hours [38].…”
Section: Diluting the Amniotic Fluidmentioning
confidence: 99%
“…The amniotic fluid is often replaced with warmed Ringer's lactate either during fetoscopy or following amniotic insufflation [27,78]. As Ringer's lactate has lower osmolarity than normal amniotic fluid, surgeons rely on fetal secretions (urine, lung, nasal, and salivary) and intramembranous reabsorption to normalize the amniotic fluid osmolarity after surgery [38,78,79,86,87]. The complete replacement of the amniotic fluid, after fetoscopy, is expected to take up to 48 hours [38].…”
Section: Diluting the Amniotic Fluidmentioning
confidence: 99%
“…De Santis et al reported that the patients with PPROM did not appear to demonstrate any benefit from this repetitive AF replacement (250 mL per intervention) as measured by post procedure AFI because fluid loss occurred within 6 h of instillation [136,149]. Locatelli et al found that the serial AI could improve the neonatal outcome primarily by prolonging latency [145,151]. The patients with PPROM and oligohydramnios had a significantly shorter interval to delivery, lower neonatal survival of 20%, 62% of pulmonary hypoplasia and 60% rate of neurological handicap.…”
Section: Amnio-infusion Techniquesmentioning
confidence: 99%
“…2. Conductor in the amniotic cavity [26] мощью коллагена, смеси тромбоцитов и фибриногена достаточно противоречивы, что требует дальнейших исследований в данном направлении и сравнения разных методик и технологий [9, [31][32][33].…”
Section: обсуждение и выводыunclassified